Downlink multiuser MIMO scheduling in LTE Advanced systems - Guosen Yue; Prasad, N.; Rangarajan, S. (2012 IEEE International Conference on Communications (ICC), 2012)
In this paper, we consider the downlink (DL) multiuser (MU) multi-input-multi-output (MIMO) scheduling for the fourth generation LTE Advanced (LTE-A) cellular networks. The DL MU-MIMO scheduling can be posed as an optimization problem to maximize the weighted sum rate subject to several practical constraints, such as a per-user rank constraint. Due to these constraints finding the optimal solution becomes an NP-hard problem. Consequently, we propose an efficient albeit sub-optimal rank balancing approach that enforces the peruser rank constraint and present several rank balancing based scheduling algorithms. We show that the proposed algorithms are guaranteed to yield constant-factor approximations. Simulation results demonstrate that the proposed rank balancing based scheduling algorithms outperform other competing schemes over various relevant system scenarios.